KARAKTERISTIK USAHA KECIL MENENGAH KOPI JAHE MANIA DI DESA LANGI KECAMATAN BOLANGITANG BARAT KABUPATEN BOLAANG MONGONDOW UTARA - Sry Melisa Ahmad; Yanti Saleh; Yuriko Boekoesoe (Universitas Negeri Gorontalo, 2017)
The purpose of this research is to know Characteristic of SME coffee ginger mania in Langi Village, West Bolangitang District, BolaangMongondow Utara Regency. This research was conducted from August to September 2017, using case study method. Sampling with Purposive Sampling technique is then obtained with a sample of 1 respondent is the owner of SMEs Coffee Ginger Mania. The type of data used is primary data and secondary data. Data analysis used is qualitative descriptive analysis. The results of this study are: 1) SME Coffee Ginger Mania as a whole employees have a productive age and can increase the production of more businesses. Furthermore, based on the level of employee education in accordance with the results of research that the level of employee education in SMEs Coffee Jahe Mania is in high school (SMA) as much as 3 (three) people. 2) The Business Capital of this SME that consists of investment capital (long-term equipment), Working Capital (raw materials) and Operational Capital (employee salary and electricity costs). 3) For every production can reach ± 50 pack / month with size 1gr with price 15.000 perbungusnya. In fulfilling the results of production here still see from the market demand. Meanwhile, for the marketing area of this product spread in District of West Bolangitang, BolangitangTimur, Kaidipang and Bintauna.